Contextualizing organizational frames: Teaching leadership to faculty in agricultural and natural resources - Caitlin Lunzmann; Nicole L. P. Stedman; Ange Asanzi; Amy C. Brown; Damilola Ajayi; Rigo A. Chaparro (Advancements in Agricultural Development, 2023)
Possessing leadership skills has been determined to be an essential requirement within the workplace. A multi-level leadership program was designed to help provide undergraduates with more exposure to leadership principles. The program team was created through the collaboration of multiple universities found within the southeastern United States. Through a 14-week online training program followed by a field experience, participants were exposed to Bolman and Deal’s organizational frames. Participants then created cased studies grounded in this leadership framework and based on the data that was collected during their field experiences. This study quantitatively analyzed the consistency with which each of the frames were used. From the 16 published case studies on the multi-institutional project’s website, assessment questions were analyzed based on which frame/frames were being referenced. Findings from this study identified a similar use of each of the frames throughout all the case studies. Further research should be conducted to better understand each participant’s comprehension of the organizational frames prior to the development of their case studies.